Environmental Influences on Fish Species Distribution in the Musolo River System, Congo River Basin (Democratic Republic of the Congo, Central Africa) - Tobit L. D. Liyandja; Armel Ibala Zamba; Channelle A. Sefu; Didier L. Dianzuangani; Ready K. Konda; Raoul J. C. Monsembula Iyaba; Justin J. M. N. Mbimbi (European Scientific Journal, ESJ, 2019)
Ichthyofaunal distribution was studied in the Musolo River system, a small affluent tributary of the Congo River flowing into Pool Malebo (Democratic Republic of the Congo). Twelve ecological stations were sampled, of which eight were located in the Musolo main-channel and four in the Fushi River, a principal tributary of the Musolo. Each station was sampled four times over a two-year period, with fishing techniques following standardized methods utilizing dip and cast nets, and nine environment variables were measured at each station. Fifty-three fish species belonging to 36 genera and 16 families were collected with the Alestidae, Distichodontidae, Cichlidae, Cyprinidae, Mormyridae, and Mochokidae being the most diversified. Redundancy Analysis with forward selection coupled with Monte Carlo permutation tests (499 permutations) identified total dissolved solid (25.8%) and altitude (24.4%) as accounting for 50.2% of total variance (p < 0.05). The contribution of the two first axes was significant (F = 3.41; p = 0.004). Species richness increases from upstream to downstream. In general, the high value of Shannon’s diversity (1.07-2.67) and Equitability European Scientific Journal November 2019 edition Vol.15, No.33 ISSN: 1857 – 7881 (Print) e - ISSN 1857- 7431 193 (0.62-0.96) indices at all sites, indicates that the examined stretch of the Musolo River system is in good ecological health, despite its location adjacent to the megacity of Kinshasa.